2016
DOI: 10.1016/j.bbamem.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysin of uropathogenic Escherichia coli: A cloak or a dagger?

Abstract: Hemolysin from uropathogenic Escherichia coli (UPEC) is a hemolytic and cytotoxic protein active against a broad range of species and cell types. Expression of hemolysin correlates with severity of infection, as up to 78% of UPEC isolates from pyelonephritis cases express hemolysin. Despite decades of research on hemolysin activity, the mechanism of intoxication and the function of hemolysin in UPEC infection remain elusive. Early in vitro research established the role of hemolysin as a lytic protein at high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 102 publications
4
69
0
12
Order By: Relevance
“…An extensive literature has reported that UPEC HlyA contributes to bladder pathology but not urinary tract colonization in mice (23,40,41). In contrast, we find that HlyA does affect bacterial loads in the murine bladder at both 1 and 3 d pi (Fig.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…An extensive literature has reported that UPEC HlyA contributes to bladder pathology but not urinary tract colonization in mice (23,40,41). In contrast, we find that HlyA does affect bacterial loads in the murine bladder at both 1 and 3 d pi (Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Several studies have demonstrated that HlyA is cytotoxic to a wide range of host cells (26,(41)(42)(43)(44). However, to our knowledge, this is the first study to survey HlyA expression levels across strains from a closely related lineage (i.e., ST131) and to associate this variation with killing of innate immune cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…coli harbors HlyA, while ∼50% of UPEC strains harbor and express HlyA, presenting a close correlation between increased clinic E . coli pathogenesis with HlyA expression [21,23,51]. In recent years, because it has been hypothesized that hemolysin is secreted at sublytic concentrations in vivo, there is increasing interest in understanding the more subtle effects of hemolysin on host cellular processes aside from outright lysis, including RhoA activation [52], Akt signaling [53], cell death pathway [22,54] and protease degradation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Here, our study adds new findings to the scenario of hemolysin-mediated biological functions by identifying that abnormal expression of hemolysin in bacteria promotes host immune recognition of replicating pathogens via non-canonical inflammasomes and restricts bacterial colonization in vivo (Fig 6). Because hemolytic proteins exhibit multilayered or even antagonistic roles in modulating host responses to infections, it is not surprising that bacteria have evolved complicated mechanisms to fine-tune the synthesis, maturation, and transport of hemolysin [21,23,51]. Thus, studies of the spatiotemporal expression of hemolysin in vivo will be essential for understanding both host defense and bacterial survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation